The Role of Scientific Language Use and Achievement Level in Student Sensemaking - Hamnell-Pamment, Ylva (International journal of science and mathematics education, 2024)
Many science students struggle with using scientific language and making sense of scientific phenomena. Thus, there is an increased interest in science education research and public policy with regard to understanding and promoting scientific language use and sensemaking in science classrooms. However, there is a lack of comparative studies on how upper-secondary school students of different achievement and language levels use scientific language to make sense of phenomena. The aim of this study was to explore the relationship between achievement level, scientific language use, and sensemaking in chemistry for students being set a sensemaking task while constructing concept maps on the topic of chemical equilibrium. The concept maps were collected from five different upper-secondary schools in Sweden from two school systems (Swedish and International Baccalaureate). Using content analysis, these concept maps were examined for scientific language use as well as structuring of sensemaking. A majority of the students had difficulty structuring sensemaking in their concept maps, independently of achievement level. These difficulties included unstructured reasoning, symbolic representations being used as explanations, surface-level learning, and linear reasoning connected to rote learning. There appeared to be a connection between learning context and student individual structuring of sensemaking as expressed in the concept maps. The results also showed a clear relationship between scientific language use and achievement level in the student sample. The results indicate that the structuring of sensemaking and scientific language use are not always connected processes. In conclusion, teachers may need to adopt a teaching practice that includes directed and differentiated support for scientific sensemaking.